Photography in relation to time and space. - Ng, Caleb Yong Chuang. (2012)
This final year project delves into traditional and alternative notions of space and time with respect to the art of photography and seeks to present the findings; demonstrating ideas and concepts of physical space within and outside the frame, as well as the notions of time and transience pertaining to the content and appreciation of photography, through a series of landscape.